Comparison of serum calcium and magnesium levels between preeclamptic and normotensive healthy pregnant women - Mittal, Shilpa; Shaikh, M. K. S.; Thakur, Ratna; Jain, Darshana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is idiopathic multisystem disorder specific to human pregnancy. Its incidence is 8-10% of total pregnancies in India. It is one of the leading causes of maternal and fetal morbidity and mortality worldwide. Alterations in serum calcium and magnesium levels have been suggested as effective factors in causing preeclampsia. The aim of this study was to compare serum calcium and magnesium levels in preeclamptic and normal pregnant women in third trimester of pregnancy. Methods: The study was conducted in the department of biochemistry in collaboration with department of obstetrics and gynaecology, Sri Aurobindo medical college & P. G. institute, Indore during the period January 2012 to January 2013. Subjects were divided into two groups: group-I included 100 preeclamptic women group-II included 100 age matched, healthy pregnant women. Serum calcium and magnesium was estimated by Arsenazo III method and by Calmagite method in ERBA CHEM-5 respectively (Enzymatic kit method). Results: Serum levels of calcium (8.27 ± 0.37 mg/dL vs. 9.06 ± 0.27 mg/dL) and magnesium (1.99 ± 0.13 mEq/L vs. 2.03 ± 0.13 mEq/L) were significantly lower in preeclamptic women than the control group (i.e. healthy pregnant women). Conclusions: Hypocalcaemia and hypomagnesaemia are seen in the preeclamptic women may be responsible for the vascular pathology associated with onset of preeclampsia. Hence it can be concluded that adjuvant supplementation of calcium and magnesium may prevent further progression of preeclampsia.